WORKING ON PERSIAN WORDS IN PRIMARY EDUCATION (International journal of artificial intelligence, 2025)
This article discusses the content of words borrowed from the Persian-Tajik language, their use in their own and figurative meanings, and the meanings used in the text, given in Chapter 1 of the fourth-grade textbook "Reading Literacy" .